2004
DOI: 10.1177/00222194040370060801
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Social Construction of LD on Culturally Diverse Families

Abstract: This response focuses on the effects of the current construction of learning disabilities (LD) on families of children from devalued racial/ethnic groups. Agreeing with the arguments of Reid and Valle, we add that parents from such groups are further disenfranchised because they are not participants in the critical discourse surrounding LD and because of the persistent belief that their parenting skills are deficient. We also suggest that the expectation of parental advocacy may be alien to parents whose cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 4 publications
0
26
0
2
Order By: Relevance
“…In fact there have been academics who have argued that disabilities such as learning difficulties, behaviour, emotional and social difficulties are socially constructed (Gabel, 2004;Hatton, 2004;Lindsay, Pather and Strand, 2006) for precisely the same reasons. It has also been suggested that the system of special education is also culturally bound and that parents from minority ethnic communities can feel disenfranchised when they encounter and access such systems (Zionts et al, 2003;Kalyanpur and Harry, 2004). However, such discussions are still relatively new when it comes to autism; and there is very little research on how parents from different cultural backgrounds interpret the defining social behaviours used to identify autism.…”
Section: Introductionmentioning
confidence: 99%
“…In fact there have been academics who have argued that disabilities such as learning difficulties, behaviour, emotional and social difficulties are socially constructed (Gabel, 2004;Hatton, 2004;Lindsay, Pather and Strand, 2006) for precisely the same reasons. It has also been suggested that the system of special education is also culturally bound and that parents from minority ethnic communities can feel disenfranchised when they encounter and access such systems (Zionts et al, 2003;Kalyanpur and Harry, 2004). However, such discussions are still relatively new when it comes to autism; and there is very little research on how parents from different cultural backgrounds interpret the defining social behaviours used to identify autism.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence that the satisfaction of parents with those teaching their children with special educational needs usually declines as the children grow older or their difficulties become more complex (Gershwin, Singer, & Draper, 2008;Leiter & Wyngaarden, 2004;Spann, Kohler, & Soenksen, 2003). It is often in these circumstances that the greatest dissatisfaction arises with education services, and above all with teachers (Kalyanpur & Harry, 2004;Tanner, 2000), except when the treatment given to children is suitable and contributes to an improvement in their academic situation (Nugent, 2007). Nonetheless, in such cases parents may still show some degree of dissatisfaction, although this is related to the lack of a participatory role offered to them as collaborators in the education provided (Seitsinger et al, 2008;Shaffer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…En esta línea, parece ser que los progenitores de niños con dificultades, inicialmente, están satisfechos con los servicios educativos existentes, así como con los profesionales que trabajan en ellos; no obstante, se ha evidenciado cómo la satisfacción de los padres con los profesores de sus hijos con necesidades educativas especiales suele decrecer a medida que el niño se hace mayor o sus dificultades son más complejas (Gershwin, Singer, y Draper, 2008;Leiter y Wyngaarden, 2004;Spann, Kohler, y Soenksen, 2003). Frecuentemente, ante estas circunstancias surgen las mayores insatisfacciones con los servicios educativos, y sobre todo con los maestros (Kalyanpur y Harry, 2004;Tanner, 2000), excepto si el tratamiento ofertado a los niños es el adecuado y contribuye a mejorar su situación académica (Nugent, 2007); sin embargo, en estos casos los progenitores también pueden mostrar cierto grado de insatisfacción, si bien ésta se relaciona con la falta de participación que se les ofrece a ellos mismos como colaboradores en la enseñanza (Seitsinger, et al, 2008;Shaffer, 2010).…”
Section: Introductionunclassified
“…They are building on the original ideas of Reid and Valle (2004), who argued that learning disabilities are not always an objective fact, but are historically and culturally determined. Kalyanpur and Harry (2004) added that culturally-diverse parents dealt with additional inequities in their struggle with the educational system on two counts: they were parents, not professionals, and culturallydiverse parents were often further excluded because of perceived poor parenting skills.…”
Section: Learning Disabilities and Cultural Assessmentmentioning
confidence: 99%
“…Still, Kalyanpur and Harry (2004) explained, even with dysfunction in families, most parents were dismayed to be faced with the fact that their children were not successful academically in school. This observation was made in relation to culturallydiverse families who had a child, or children, with learning disabilities.…”
Section: O Verall Themesmentioning
confidence: 99%